Expanding the phenotype of biallelic loss‐of‐function variants in the NSUN2 gene: Description of four individuals with juvenile cataract, chronic nephritis, or brain anomaly as novel complications. Issue 1 (20th October 2020) - Kato, Kohji; Mizuno, Seiji; Morton, Jenny; Toyama, Miho; Hara, Yuichiro; Wasmer, Evangeline; Lehmann, Alan; Ogi, Tomoo
Abstract: The NSUN2 gene encodes a tRNA cytosine methyltransferase that functions in the maturation of leucyl tRNA (Leu) (CAA) precursors, which is crucial for the anticodon‐codon pairing and correct translation of mRNA. Biallelic loss of function variants in NSUN2 are known to cause moderate to severe intellectual disability. Microcephaly, postnatal growth retardation, and dysmorphic facial features are common complications in this genetic disorder, and delayed puberty is occasionally observed. Here, we report four individuals, two sets of siblings, with biallelic loss‐of‐function variants in the NSUN2 gene. The first set of siblings have compound heterozygous frameshift variants: c.546_547insCT, p.Met183Leufs*13; c.1583del, p.Pro528Hisfs*19, and the other siblings carry a homozygous frameshift variant: c.1269dup, p.Val424Cysfs*14. In addition to previously reported clinical features, the first set of siblings showed novel complications of juvenile cataract and chronic nephritis. The other siblings showed hypomyelination and simplified gyral pattern in neuroimaging. NSUN2 ‐related intellectual disability is a very rare condition, and less than 20 cases have been reported previously. Juvenile cataract, chronic nephritis, and brain anomaly shown in the present patients have not been previously described. Our report suggests clinical diversity of NSUN2 ‐related intellectual disability.